More than just Students: A Description of Psychological Well-Being in Students with Dual Roles - Annisa Najwa Saputri; Deby Inasya Hanifa; Jeanne Meilyra Arnettasari; M. Aldy Bukhori; Maura Indah Islami; Muhammad Luqman; Siti Sauva Salsabilla; Ermina Istiqomah; Rahmi Fauzia; Risna Febriani (Universitas Katolik Soegijapranata, 2025)
This research focuses on the phenomenon of psychological well-being among students who play a dual role, namely studying while working. This study was conducted in two cities, namely Banjarbaru and Banjarmasin, South Kalimantan, and aims to further describe the dimensions of psychological well-being that influence students who have dual roles. This study used a qualitative method with a phenomenological approach using interviews with three people with purposive sampling. The research findings indicate that students experience various challenges in carrying out dual roles, especially in managing time. The dimensions of psychological well-being are influenced by several factors such as authority structure, adaptability, time management, long-term perspective, and self-acceptance. The results also indicate that social support plays a significant role in improving students' psychological well-being.